Strategi Peningkatan Mutu Pembelajaran Agama Hindu Di Sekolah Luar Biasa C Negeri Bangli - Sudana, I Made; Sudarsana, I Ketut; Setyaningsih, . (Jurnal Penjaminan Mutu, 2018)
Selection and application of specific learning strategies to study religion. Likewise, learning with Hinduism learning strategies at Sekolah Luar Biasa C Negeri Bangli, with their disability from mental and weak dimensions or low IQ, the right strategy and in accordance with the student's background is one of the determining factors for achieving goals and the spirit of the learning process itself.The results of the study show the following results: Strategy of learning Hinduism in Special Schools C Country Bangli is an individual learning strategy (individual learning) and exposition learning learning strategies. The stages of learning Hinduism in Sekolah Luar Biasa C Negeri Bangli are: 1) student factors, students often desire themselves and are difficult to regulate; 2) teacher factors, teachers who often have difficulty understanding students from different IQ levels of students; 3) School factors, lack of educators, facilities and planning make the teaching and learning process stunted, especially lack of learning media facilities. Efforts made in learning Hinduism in Special Schools in Bangli State C are as follows: 1) attachment of special educators to Hinduism educators; 2) Provide special educatio n to teaching staff such as for special education for Sekolah Luar Biasa C Negeri Bangli; 3) the teacher simplifies learning so that students have more material provided by the teacher; 4) The school strives for the appointment of classrooms, provides learning media with interesting drawings, gives more attention and prepares students from facilities in learning, and provides special learning programs for SLB C / Mentally disabled children, namely self-development and self-development.